Agrohomeopathy as an alternative for the control of Plasmodiophora brassicae in Brassicaceae under greenhouse conditions - Rodríguez-García, Daniela (2025)
Introduction. Horticultural crops within the Brassica genus (such as broccoli and cabbage) are affected by Plasmodiophora brassicae, a pathogen that causes the disease known as clubroot. Agrohomeopathy has shown positive effects on plant growth and disease control in some cases. Objective. The study evaluated the use of agrohomeopathic treatments, specifically fitonosodes, to combat clubroot disease caused by Plasmodiophora brassicae in cauliflower and cabbage. Materials and methods. The experiments were conducted in a greenhouse using both sterile and non-sterile soils, applying fitonosodes and succussed water. The variables assessed included leaf and root length, fresh and dry biomass, and disease severity. Results. In cauliflower, the Water_2 treatment in non-sterile soil achieved the greatest root length (139 cm), while treatment Fitonosode_5 in sterile soil produced plants with the highest leaf length (353 cm). In non-sterile soil, no significant differences were found between treatments for either variable. In cabbage, Water_2 in non-sterile soil also showed the best root length (139 cm), and in sterile soil, Water_2 and Fitonosode_5 achieved the greatest leaf heights, with 335 cm and 305 cm, respectively. In non-sterile soil, Water_2 reached 227 cm in leaf height, significantly outperforming other treatments. Regarding disease severity, Fitonosode_5 significantly reduced the incidence, maintaining over 80% of cauliflower and 90% of cabbage in low severity categories, indicating improved plant health. Conclusions. These findings suggest that agrohomeopathy (particularly the fitonosodes), could be an effective and promising alternative for controlling P. brassicae, contributing to improved physiological and structural development of crops.